Landscape and Design Elements Involved in the Building of the Temple of Saint Michael Archangel, Santo Domingo of Heredia, Costa Rica, 1879 - Vargas Benavides, Henry O. (2018)
This document analyzes the landscape and design elements involved in the building of the patrimonial temple El Carmen of Santo Domingo of Heredia (former chapel of San Miguel) during the XIX century in Santo Domingo of Heredia. Theories of design and semiotics are employed with the aim of performing a visual and textual comparison along with the founding text of the temple of Saint Michael, the pastoral letters of Monsignor Augusto Thiel, field interviews, and the two most representative religious images of the temple, its patron saints. The goal will be the symbolic representation of the landscape and of the power elements in an adobe building at the end of the XIX century in Costa Rica.